Changes in winter storm characteristics and lake-effect snow in convection-permitting regional climate simulations in the U.S. - Riesenberg, Mark Ryan, author; Rasmussen, Kristen L., advisor; Schumacher, Russ S., committee member; Fassnacht, Steven R., committee member (Colorado State University. Libraries, 2019)
Lake-effect snowfall events have extreme regional impacts with some of the largest snowfall totals on record. Previous studies hypothesize that in a future climate, less ice coverage will be present over the Great Lakes in winter, allowing for more latent and sensible heat fluxes released into the atmosphere. An investigation of the changes in winter season precipitation systems, including lake-effect snowstorms, uses two convection-permitting regional climate continuous 13-year simulations driven by: (1) ERA-Interim reanalysis and (2) ERA-Interim reanalysis plus a climate perturbation for the RCP8.5 scenario. These simulations are used to investigate meteorological and land surface changes in a future climate during the winter months across the U.S. Results from this study show that weak precipitation decreases, while moderate to stronger precipitation is enhanced in a future climate with strong signals over the Great Lakes. Therefore, a lake-effect snowstorm event in the Great Lakes region is used to examine the effects of a warming climate on mesoscale lake-effect snowstorm dynamics and their regional impacts. Analysis of these simulations shows that lake-effect snowstorms in a future climate may have enhanced snow accumulations downwind of the lakes due to more frequent ice-free conditions of the Great Lakes. Enhanced latent and sensible heat fluxes, as a result of less ice-coverage, add moisture and energy to the atmosphere to enhance storm development. The increase in surface fluxes are important for meteorological processes within the planetary boundary layer, which interact with the overlaying atmosphere. These interactions may change the mechanisms that are important for lake-effect snowfall events, such as the 850 mb to surface temperature differences, relative humidity, layer instability, and surface pressure. In addition, less ice coverage may enhance mesoscale circulations due to the thermal contrast (i.e., land-lake breeze) and differential surface roughness. This research will improve our understanding of the question, "What will today's weather look like in a future, warmer climate?" to examine possible socioeconomic and public safety implications of changing precipitation patterns in the winter season.